Status And Legal Relationship Between Plasma Farmers And Core Companies In Partnership Agreements (Case Study At Pt. Sierad Produce, Tbk Div. Partnership) - Evita Vibriana Wulandari; Faisal Santiago; Suparno Suparno (CV. Publikasi Indonesia, 2023)
In this study, the authors used empirical legal research methods based on primary data sources based on field research on partnership agreements, interviews with users. Secondary data is literature study by reading and studying and understanding literature books as well as the knowledge gained during lectures. In addition to conducting interviews and observations. The analysis used was descriptive qualitative, namely a data analysis method that classifies and selects data obtained from field research according to its quality and truth, then linked with theories, principles and legal principles obtained from literature studies so that answers are obtained. formulated problem. Theory used: 1. Grand Theory (Theory of Legal Relations); According to R. Soeroso: Legal relationship is a relationship between two or more legal subjects. In this legal relationship, the rights and obligations of one party deal with the rights and obligations of the other party. That the law regulates the relationship between one person and another, between people and society is regulated by law. Whoever disturbs or ignores this relationship, then he can be forced by law to respect it. So every legal relationship has two aspects: the aspect of